Development and performance evaluation of an innovative community-scale single-pillar pyrolysis reactor for converting plastic waste into alternative liquid fuel - Thathong, Vanlop; Boonnuk, Tanunchai; Tantamsapya, Netnapid; Phimpabut, Nuwut (Creative Science, 2026)
Plastic waste accumulation has become a critical global environmental challenge due to the increasing generation of non-recyclable plastics and the growing demand for sustainable waste-to-energy technologies. This study developed and evaluated an innovative community-scale single-pillar pyrolysis reactor for converting non-recyclable polypropylene (PP) and polystyrene (PS) waste into alternative liquid fuel under catalyst-free, oxygen-limited conditions. The system integrates a pyrolysis chamber, an externally heated combustion chamber fueled by waste lubricating oil, a vertical water-cooled condenser, and a vapor-recycling unit into a compact configuration suitable for decentralized applications. Reactor performance was evaluated using two PP:PS feedstock compositions (50:50 and 60:40, w w-1). Each batch processed 10 kg of plastic waste (n = 3), producing 8.03 – 8.27 L of pyrolysis oil within 190 – 200 min. The 60:40 feedstock yielded numerically higher liquid fuel production (67.00 ± 1.91 wt.%), fuel conversion efficiency (73.85 ± 2.31%), oil productivity (3.73 ± 0.23 L h⁻¹), and higher heating value (45.73 ± 0.23 MJ kg⁻¹), together with a lower estimated gas yield (23.73 ± 2.16 wt.%). However, these differences were not statistically significant (p > 0.05), indicating stable and reproducible reactor performance across both feedstock compositions. Field validation following technology transfer was conducted in 19 communities in Loei Province, Thailand. The system achieved an average plastic reduction efficiency of 92.96 ± 0.87%, reduced accumulated plastic waste by 55.51 ± 22.41%, and demonstrated successful utilization of the recovered fuel in agricultural machinery and municipal crematoriums. These findings demonstrate that the proposed single-pillar reactor provides a practical, low-cost, and scalable decentralized waste-to-energy technology that supports circular economic implementation and sustainable community-based plastic waste management. GRAPHICAL ABSTRACT HIGHLIGHTS A single-pillar reactor converted PP–PS waste into alternative liquid fuel. Liquid fuel yield reached 67.00 wt%, with plastic reduction above 90%. Pyrolysis oil achieved a heating value of up to 45.73 MJ kg⁻¹. Blended fuels operated successfully in agricultural equipment. The reactor was validated across 19 communities in Thailand.